Implementing mental health in practice : strategies to engage patients and families. Disruptive behavior and aggression - Bauer, Nerissa S.; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2015)
This video focuses on using motivational interviewing techniques to identify and address disruptive behavior and aggression. In the case demonstrated, Dennis, a 3-year-old boy, is referred to you by his Head Start program for fighting. His mother tells you he has previously been "kicked out" of 2 child care centers for the same problem. She frequently criticizes him as she relays the history of his problems and periodically gives him orders in an angry tone of voice. He has frequent tantrums, and his mood seems to change quickly. Because of these symptoms, his mother expresses concerns about the possibility of bipolar disorder, which she reports "runs in the family".
Presenter: Nerissa S. Bauer.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 19, 2020)
Keywords: Behavior disorders in children; Problem children -- Functional assessment; Aggressiveness in children; Documentary films; Educational films; Nonfiction films; Internet videos; Streaming video; Short films